Comment on “Fuzzy mathematical programming for multi objective linear fractional programming problem” - Stanojević, Bogdana; Stanojević, Milan (Fuzzy sets and systems, 2014)
Chakraborty and Gupta, in their paper “Fuzzy mathematical programming for multi objective linear fractional programming problem”, published in Fuzzy Sets and Systems 125 (2002), claimed that their methodology proposed for solving multi objective linear fractional programming problem always yields an efficient solution. This paper indicates that their claim is generally wrong and this is due to the non-equivalence of the original problem and the associated linear problem.